Reactive hyperemia response and ultrasonographic features in determining tissue recovery in rats - Yapp, Jong Heng (2018)
Frequent repositioning of patient is important to relief pressure and correct damages on skin areas induced by pressure in order to avoid pressure ulcer (PU) development. Prolonging the recovery time for pressure relief may be beneficial but the amount of recovery time is unknown and worth investigating. In this study, the relationship between different recovery time and weight-bearing tissue conditions subjected to repetitive loading is investigated through histopathology examination in animal model using Sprague-Dawley rats. Furthermore, the effect of different recovery times on non-invasive PU indicators using peak reactive hyperemia (RH) trend and ultrasonographic (US) features are investigated. The hypothesis being tested is that different recovery time that simulates insufficient and sufficient recovery time could affect the RH trend and US feature. This study also compares the peak RH trends and US features with the tissue condition under histopathological examination to determine the potential use of these features in determining the adequate amount of recovery time of weight-bearing tissue in rats non-invasively. Twenty-one male Sprague-Dawley rats (seven per group), with body weight of 385-485g, were categorised into three groups and subjected to different recovery times, each with three repetitive loading cycles at skin tissues above of right trochanter area. The first, second, and third groups were subjected to short (3 min), moderate (10 min), and prolonged (40 min) recovery, respectively, while applying fixed loading time and pressure (10 min and 50 mmHg, respectively). Peak RH was measured during the three cycles to determine RH trend (increasing, decreasing, and inconsistent). All rat tissues at the trochanter area were evaluated using ultrasound at pre- and post-experiment and rated by two raters to categorise the severity of tissue changes (no, mild, moderate, and severe change). The tissue condition was also evaluated using histopathological examination to distinguish between normal and abnormal tissues. It was found that as the recovery time increases (3 min vs. 10 min vs. 40 min), the number of samples with normal tissue (43% vs. 43% vs. 100.00%) and inconsistent RH response trend (29% vs. 57% vs. 72%) also increases. In addition, as the recovery time decreases (40 min vs. 10 min vs. 3 min), there is an increased number of samples with abnormal tissue (0% vs. 57% vs. 57%) and increasing RH response trend (14% vs. 29% vs. 57%). Subsequently, most of the samples with increasing RH trend is related to abnormal tissue (71%); while inconsistent RH trends is more related to normal tissue (82%). However, the recovery time has no effect to the tissue condition evaluated under ultrasonographic. Moreover, there is no relationship between the tissue conditions evaluated under ultrasonographic and histopathological examination. The results suggest that different recovery times affect the tissue condition and RH response trend during repetitive loading. In addition, RH trend over repetitive loading may serve as a new feature for determining tissue condition that leading to pressure ulcer. This animal study may be extended to human studies in the future.